The impact of European integration on the economic security of business in Ukraine - Bogma, Olena; Silakova, Hanna; Vialets, Oksana (My University, 2022)
У статті обґрунтовано актуальність дослідження впливу євроінтеграції України на рівень економічної безпеки вітчизняних підприємств як центральної ланки економічної системи країни. Систематизовано позитивні та негативні наслідки впливу євроінтеграційного процесу на економічну безпеку бізнесу в Україні. Визначено основні сценарії впливу процесу євроінтеграції України на економічну безпеку її бізнесу, розглянуто їх зміст, встановлено напрямки позитивних та негативних змін для економічної безпеки підприємств у розрізі окремих сценаріїв. . Визначено основні внутрішні та зовнішні чинники, що гальмують процес євроінтеграції України. The article substantiates the relevance of studying the impact of European integration of Ukraine on the level of economic security of domestic enterprises as a central link in the country's economic system. The positive and negative consequences of the influence of the European integration process on the economic security of business in Ukraine are systematized. The main scenarios of the impact of the process of European integration of Ukraine on the economic security of its business are determined, their content is considered, the directions of positive and negative changes for the economic security of enterprises in the context of certain scenarios are established. The main internal and external factors that hinder the process of European integration of Ukraine have been identified.
Keywords: Євроінтеграція; економічна безпека підприємства; загроза; бізнес; можливості; сценарій; European integration; economic security of an enterprise; threat; business; opportunities; scenario